Changes of aliphatic C–H bonds in cyanobacteria during experimental thermal maturation in the presence or absence of silica as evaluated by FTIR microspectroscopy. Issue 4 (5th June 2018) - Igisu, Motoko; Yokoyama, Tadashi; Ueno, Yuichiro; Nakashima, Satoru; Shimojima, Mie; Ohta, Hiroyuki; Maruyama, Shigenori
Abstract: Aliphatic C–H bonds are one of the major organic signatures detected in Proterozoic organic microfossils, and their origin is a topic of interest. To investigate the influence of the presence of silica on the thermal alteration of aliphatic C–H bonds in prokaryotic cells during diagenesis, cyanobacteria Synechocystis sp. PCC6803 were heated at temperatures of 250–450°C. Changes in the infrared (IR) signals were monitored by micro‐Fourier transform infrared (FTIR) spectroscopy. Micro‐FTIR shows that absorbances at 2, 925 cm −1 band (aliphatic CH2 ) and 2, 960 cm −1 band (aliphatic CH3 ) decrease during heating, indicating loss of the C–H bonds, which was delayed by the presence of silica. A theoretical approach using solid‐state kinetics indicates that the most probable process for the aliphatic C–H decrease is three‐dimensional diffusion of alteration products under both non‐embedded and silica‐embedded conditions. The extrapolation of the experimental results obtained at 250–450°C to lower temperatures implies that the rate constant for CH3 ( k CH 3 ) is similar to or lower than that for CH2 ( k CH 2 ; i.e., CH3 decreases at a similar rate or more slowly than CH2 ). The peak height ratio of 2, 960 cm −1 band (CH3 )/2, 925 cm −1 band (CH2 ; R 3/2 values) either increased or remained constant during the heating. These results reveal that the presence of silica does affect the decreasing rate of the aliphatic C–H bonds in cyanobacteria during thermal maturation, but that it does not significantly decrease the R 3/2 values. Meanwhile, studies of microfossils suggest that the R 3/2 values of Proterozoic prokaryotic fossils from the Bitter Springs Group and Gunflint Formation have decreased during fossilization, which is inconsistent with the prediction from our experimental results that R 3/2 values did not decrease after silicification. Some process other than thermal degradation, possibly preservation of specific classes of biomolecules with low R 3/2 values, might have occurred during fossilization.